Topology optimization of binary structures under design-dependent fluid-structure interaction loads - Picelli, R.; Ranjbarzadeh, S.; Sivapuram, R.; Gioria, R. S.; Silva, E. C. N. (Structural and multidisciplinary optimization, 2020)
A current challenge for the structural topology optimization methods is the development of trustful techniques to account for different physics interactions. This paper devises a technique that considers separate physics analysis and optimization within the context of fluid-structure interaction (FSI) systems. Steady-state laminar flow and small structural displacements are assumed. We solve the compliance minimization problem subject to single or multiple volume constraints considering design-dependent FSI loads. For that, the TOBS (topology optimization of binary structures) method is applied. The TOBS approach uses binary {0,1} design variables, which can be advantageous when dealing with design-dependent physics interactions, e.g., in cases where fluid-structure boundaries are allowed to change during optimization. The COMSOL Multiphysics software is used to solve the fluid-structure equations and output the sensitivities using automatic differentiation. The TOBS optimizer provides a new set of {0,1} variables at every iteration. Numerical examples show smoothly converged solutions.